2015
DOI: 10.1111/jtm.12203
|View full text |Cite
|
Sign up to set email alerts
|

Myiasis in Travelers

Abstract: This is the largest myiasis case series in ill returning travelers. Myiasis is not a rare dermatologic complaint with most Israeli cases imported from Latin America and specifically the Madidi National Park in Bolivia. Treatment is based on full extraction of the larva after which no antibiotic treatment is needed. Myiasis is a preventable disease and travelers should be informed of the different preventive measures according to their travel destination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 23 publications
0
59
0
4
Order By: Relevance
“…1 Although relatively rare in humans, Cutaneous myiasis is a well-documented diagnosis in travelers returning from tropical countries and has been described in head and neck cancers superimposed on cutaneous malignancies. 3,4 Although nasal, oropharyngeal, and orotracheal myiasis cases are occasionally reported, tracheopulmonary infections, especially in a patient without a recent travel history, are rare. The first reported case of pulmonary myiasis was described in 1966.…”
Section: Discussionmentioning
confidence: 98%
“…1 Although relatively rare in humans, Cutaneous myiasis is a well-documented diagnosis in travelers returning from tropical countries and has been described in head and neck cancers superimposed on cutaneous malignancies. 3,4 Although nasal, oropharyngeal, and orotracheal myiasis cases are occasionally reported, tracheopulmonary infections, especially in a patient without a recent travel history, are rare. The first reported case of pulmonary myiasis was described in 1966.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown myiasis to be 1 of the 5 most common dermatologic conditions acquired while traveling, representing 6% to 11% of cases. 50,51 However, cases of myiasis in individuals from nonendemic regions of North America without a significant travel history have also been reported. 49 Cutaneous myiasis presents in 1 of 3 ways: furuncular, migratory, or wound, depending on the infesting larvae.…”
Section: Balamuthiamentioning
confidence: 96%
“…Nevertheless, this comparative series also helps to differentiate both forms of myiasis in terms of localization, number of lesions, and median duration. 2 Interestingly, three cases were caused by Cordylobia rodhaini acquired in Ghana. This species is less common and has been rarely studied.…”
Section: Tungiasis Myiasis and Leishmaniasismentioning
confidence: 99%
“…[1][2][3][4][5] Dermatoses accounted for 19.5% of travel-related illness in the most recently published GeoSentinel study, where the three leading causes of skin consultations were skin and soft tissue infections (SSTI), insect bites, and cutaneous larva migrans. 6 Given the importance of dermatological conditions among travelers, we thus highlight here the most recent developments regarding these skin diseases to improve their prevention and post-travel management.…”
mentioning
confidence: 99%